Unusual lymphatic spread: Autopsy report of rectal obstruction from high-grade micropapillary urothelial carcinoma in the urinary bladder - Takashi Ando; Shinichi Morita; Makoto Naito (Urology Case Reports, 2024)
Bladder cancer commonly metastasizes to the lymph nodes. Rectal obstruction (RO) caused by bladder cancer has been reported rarely, and its underlying mechanism remains unclear. Herein, we present an autopsy case of a 67-year-old man with RO caused by urothelial carcinoma (UC) with a micropapillary variant in the bladder. The autopsy showed high-grade UC infiltrating the rectum via the bladder's lateral pedicle, and widely spreading within the retroperitoneum due to lymphatic dissemination. Given that RO caused by bladder cancer is typically diagnosed after it has become a systemic disease, it is crucial to consider systemic treatment for the patient.